The Effect of Performance Assessment and Incentives on Increasing Employee Achievement in PT. Indonesia Asahan Aluminium - Nadia Ika Purnama (AIBPM Publisher, 2021)
The importance of human resources for companies because it is the main factor where they have different emotions, feelings, desires and abilities, from which they have grown and developed so that a good level of work productivity can be achieved. Thus, it is necessary to integrate these aspects according to the needs of the organization. In this research will be discussed about performance appraisal and incentives as independent variables and work performance as the dependent variable with research at PT. Indonesia Asahan Aluminum. While the formulation of the research problem is: